A pilot study investigating the effects of rhythmic sensory stimulation with low-frequency sounds on depression. Issue 1 (1st June 2016) - Janzen, Thenille Braun; Rotzinger, Susan; Giacobbe, Peter; Downar, Jonathan; Kennedy, Sidney; Bartel, Lee
Abstract : Background : Rhythmic Sensory Stimulation (RSS) is a noninvasive treatment that indirectly stimulates neuronal oscillatory coherence based on the premise that the spontaneous electrical activity of the brain synchronizes to external periodic stimuli. Despite successful applications of RSS in pilot studies with Parkinson's disease and Fibromyalgia, it is not well understood whether RSS would be effective to treat other conditions associated with neural dysregulation, such as Major Depressive Disorder (MDD). Objective : This pilot study examined the effects of RSS with low-frequency sounds on MDD. Methods : Patients undertook 30 min of daily treatment for 5 weeks, concomitant with standard care. Treatment consisted of rhythmic vibroacoustic stimulation embedded in a relaxing music especially composed to reinforce gamma frequencies, particularly 40 Hz. Discussion/Conclusion : Preliminary results of the effect of RSS on depression severity and quality of life will be discussed. We expect that these initial findings will instigate further clinical trials.